2021
DOI: 10.1111/cge.13931
|View full text |Cite
|
Sign up to set email alerts
|

A new case of Smith‐Kingsmore syndrome with somatic MTOR pathogenic variant expands the phenotypic spectrum to lateralized overgrowth

Abstract: Smith‐Kingsmore syndrome (SKS) is a rare autosomal dominant disorder caused by heterozygous germline activating pathogenic variants in mammalian target of rapamycin (MTOR) on chromosome 1p36. A few patients with disseminated mosaicism have been described so far and they seem to display a different phenotype when compared to germline cases. Here we report the sixth case with a disseminated mosaic MTOR pathogenic variant, a 7‐year‐old boy with hemimegalencephaly, epilepsy, developmental delay, hypomelanosis of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Therefore, in our case, the patient exhibited HME, capillary malformation, and length discrepancy of the feet, revealing an unexpected phenotypic feature that expands the known phenotype associated with AKT3-related conditions. Additionally, this underscores the phenotypic overlap among syndromes associated with the PI3K-AKT-mTOR pathway, as evidenced by the similarity to the clinical case described by Carli et al 40…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, in our case, the patient exhibited HME, capillary malformation, and length discrepancy of the feet, revealing an unexpected phenotypic feature that expands the known phenotype associated with AKT3-related conditions. Additionally, this underscores the phenotypic overlap among syndromes associated with the PI3K-AKT-mTOR pathway, as evidenced by the similarity to the clinical case described by Carli et al 40…”
Section: Discussionsupporting
confidence: 77%
“…Finally, Alcantara et al 8 showed that vascular malformations are common features of AKT3-related disorders, but, unlike PIK3CArelated disorders, they are rarely associated with somatic overgrowth or tissue hypertrophy. For example, the clinical case described by Carli et al, 40 involving a 7-year-old boy with HME, generalized tonic seizures, mild developmental delay, lateralized overgrowth, and Ito hypomelanosis, and a mosaic variant in MTOR, confirmed the presence of these features not only in PTENopathies but also in the spectrum of mTOR-related conditions. Notably, this characteristic had not been previously reported in AKT3-related cases.…”
Section: Discussionmentioning
confidence: 82%
“…Heterozygous de novo or inherited gain-of-function (GOF) pathogenic variants of the MTOR gene underlie SKS. SKS was first described a decade ago 1,2 , and since then over 70 patients representing 26 unique alleles have been reported, with the p.Glu1799Lys allele comprising nearly half of all reported cases [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . While the majority of them are germline mutations, several somatic cases have recently been reported.…”
Section: Introductionmentioning
confidence: 99%